VARAKHSHA MONUMENT - IN THE RESEARCH OF ARCHAEOLOGISTS (Conferencea, 2022)
In this article, the Varakhsha monument, which is considered one of the ancient fortresses of Bukhara, and its structure, history of study and consistent study by archaeologists, Varakhsha murals are scientifically analyzed.